Quality of Primary Health Care for children and adolescents living with HIV - Leticia do Nascimento; Cristiane Cardoso de Paula; Tania Solange Bosi de Souza Magnago; Stela Maris de Mello Padoin; Erno Harzheim; Clarissa Bohrer da Silva (Revista Latino-Americana de Enfermagem)
Abstract Objective: to evaluate the quality of health care for children and adolescents living with HIV, among the different types of Primary Health Care services of Santa Maria, Rio Grande do Sul. Method: cross-sectional study, developed with 118 Primary Health Care professionals. The Primary Care Evaluation Instrument, Professional version, was used. For verification of the variables associated with the high score, Poisson Regression was used. Results: the professionals of the Family Health Strategy, when compared to those of the Primary Health Units, obtained a greater degree of orientation to primary care, both for the overall score and for the derived attributes score, as well as for the integrality and community orientation attributes. A specialization in Primary Health Care, other employment and a statutory work contract were associated with quality of care. Conclusion: the Family Health Strategy was shown to provide higher quality health care for children and adolescents living with HIV, however, the coverage is still low. The need was highlighted to expand this coverage and invest in vocational training directed toward Primary Care and making the professionals effective, through public selection procedure, as well as an improvement program that recognizes the care requirements, in these settings, of children and adolescents infected with HIV.